An Examination of Umar bin Khattab's Policy on Zakat as a Social Security Net in the Context of Post-Covid-19 Pandemic in Indonesia - Putri sholihatuz Zahra; Nurizal I smail (Publikasi Indonesia, 2024)
The COVID-19 pandemic has led to an unprecedented economic crisis, causing millions of people to face job losses, business closures, and financial hardship. To prevent impacts on vulnerable populations, it is essential to have a strong social safety net in the face of these difficulties. The purpose of this study is to examine the potential of zakat, the obligation of Islam to redistribute wealth, as an innovative social safety net, based on the policies of Umar bin Khattab, the second Islamic Caliph. By exploring Umar's visionary approach to zakat distribution and its relevance in contemporary times, this study examines how zakat can be used as an effective mechanism to alleviate the economic consequences of the COVID-19 pandemic for those most affected. This research uses a qualitative research approach By integrating insights from contemporary case studies and stakeholder consultations, this research proposes a comprehensive framework for implementing a robust zakat distribution system that is aligned with the United Nations Sustainable Development Goals (SDGs). This emphasizes the importance of transparent governance, accountability mechanisms, and the involvement of Islamic financial institutions, non-governmental organizations (NGOs), and community-based organizations in the zakat management process. Ultimately, this study offers an interesting case for reviving the spirit of Umar bin Khattab's zakat policy, showing how this ancient Islamic practice can serve as a powerful tool to promote financial inclusion, foster economic resilience, and support sustainable development in the face of modern crises such as the Covid-19 pandemic.